Pengembangan Aplikasi Online Logistik Internal Sentrum Agraris Lotta - Lohonauman, Charlie A. P.; Sitanayah, Lanny; Sanger, Junaidy B.; Rahardiyan, Dino; Moko, Emma M.; Kawatak, Steven Y. (Ikatan Ahli Informatika Indonesia, 2025)
Technological developments are currently felt in various fields, ranging from education to industry, and even agriculture. Logistics is a knowledge that is devoted to all activities in a place where all these activities are related to the process of selling, requisitioning goods, moving goods, transportation of goods, management, and storage of goods/products. Sentrum Agraris Lotta is a foundation operating in the agricultural sector, which currently has 5 groups of farmers, each consisting of 15 people. Increasing production results and demand for incoming and outgoing goods have led Sentrum Agraris Lotta, especially the warehouse department, to collect logistical data. Sentrum Agraris Lotta needs an application that can improve performance and make it easier for the warehouse to carry out the process of managing logistics data (management and storage of goods/products) made online with a web platform, so that it can be accessed from anywhere with different devices. The internal logistics online application was built and socialized to users through training. The training was conducted at Sentrum Agraris Lotta and attended by 10 people, including application users who act as admins, staff, and several people from Sentrum Agraris Lotta’s community. After the training, application users provided feedback in the form of the User Acceptance Test. Based on the results obtained, it can be concluded that the application built can overcome the problems faced by Sentrum Agraris Lotta, namely logistics data collection, reporting, and product data search.